2006
DOI: 10.1016/j.chemphys.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Optical activity in the Drude helix model

Abstract: An old classical one-particle helix model for optical activity, first proposed by Drude, is reconsidered here. The quantum Drude model is very instructive because the optical activity can be calculated analytically without further approximations apart from the Rosenfeld long wavelength approximation. While it was generally believed that this model, when treated correctly, is optically inactive, we show that it leads to optical activity when the motion of the particle is quantum mechanically treated. We also fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The formation of helical patterns and structures is common in many natural systems ranging from DNA molecules and amino-acids to non-neutral plasmas trapped in magnetic fields [1] and self-assembled configurations of charged particles confined in nanotubes [2]. Studying the motion of particles confined in a helix has proven to be a useful tool for the understanding of complex phenomena such as the optical activity of sugar solutions [3,4]. Certainly the problem of the confined motion of particles in a helical manifold is of fundamental interest since it reveals many intriguing phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of helical patterns and structures is common in many natural systems ranging from DNA molecules and amino-acids to non-neutral plasmas trapped in magnetic fields [1] and self-assembled configurations of charged particles confined in nanotubes [2]. Studying the motion of particles confined in a helix has proven to be a useful tool for the understanding of complex phenomena such as the optical activity of sugar solutions [3,4]. Certainly the problem of the confined motion of particles in a helical manifold is of fundamental interest since it reveals many intriguing phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been thought that the notion of coupled oscillators is a necessary condition for the explanation of the rotatory power, until the Condon, Altar and Eyring model [5] demonstrated optical activity using a quantum mechanical single-oscillator model. In the 1970s, however, it was shown [8] that the Drude model exhibits optical activity in the nonlinear regime and recently 3 it has been demonstrated that it leads to optical activity if the motion of the particle is treated quantum mechanically [9].…”
Section: Introductionmentioning
confidence: 99%